A Study of Piano Pedagogy Course Content at Undergraduate Level in Thailand - Tayrattanachai, Ni-on; Trakarnrung, Somchai (Fine Arts Journal: Srinakharinwirot University, 2015)
The purpose of this research is to study and investigate piano pedagogy core course content for undergraduate level based on the perspectives of Thai piano teachers focusing on a specific area of core course content in piano pedagogy. To investigate the answer to the question, çWhat is the core course content for piano pedagogy courses in Thailand?é, the methodology of qualitative research is employed to acquire in-depth information from fourteen participants. Participants of this study are experienced piano teachers. They were selected based on the criteria of Thai nationality and expertise. However, in order to create a suitable content for piano pedagogy students in Thailand, some current issues related to piano pedagogy in Thailand such as the cultural background, the context of teaching and learning piano in Thailand, and the issue of Thai piano teachers and students are reflected in the study. The results of this research are advantageous to piano teachers and piano pedagogues who apply this content to their teaching, as well as to the institutions interested in establishing or revising their undergraduate piano pedagogy courses and programs. The content will influence the preparation of quality piano teachers and music teachers in the future. Moreover, the study will prove helpful in preparing piano teachers for a successful teaching career.